Promoting the Importance of Understanding Children's Rights from an Early Age: Development of the Kolak Digital Game - Alfiana Falan Syarri Auliya; Anggita Gunati Fashlah; Nashrul Shavroniando Azmil Umuri; Willy Jordan Fazza Rino; Intan Amelia Sari (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Children’s rights are a fundamental part of human rights that must be protected, fulfilled, and guaranteed from an early age. However, violations of children’s rights continue to increase despite the implementation of various protection policies and programs. One possible solution is to enhance the awareness and understanding of families, particularly parents and children, regarding the importance of children’s rights. This study aims to analyze a collaborative digital storytelling game called Kolak (Collaboration between Children and Families) as an educational medium to introduce children's rights while encouraging active involvement of parents and children. The research applied a research and development (R&D) approach called as SAM model. The instruments used in this study were questionnaires for both preliminary studies and expert judgement, while the analysis technique used was quantitative descriptive analysis. Findings indicate that more than 80% of parent respondents acknowledge the importance of fulfilling children’s rights, yet there is still a lack of media that accommodates parent–child collaboration. This research has implications for the need to integrate digital learning media such as the Kolak game in early childhood education to instill an understanding of children's rights in an interesting, contextual, and developmentally appropriate manner.